Impact of a Novel Interventional Platform and Hospital Design on the Door-to-balloon Time in Patients Presenting With ST-segment Elevation Myocardial Infarction. Issue 1 (March 2015) - Poulin, Marie-France; Appis, Andrew; Purim-Shem-Tov, Yanina; Schaer, Gary L.; Snell, Jeffrey
<x xml:space="preserve">Abstract</x> Introduction: Reducing door-to-balloon (DTB) time in ST-segment elevation myocardial infarction improves outcomes. Several hospital factors can delay DTB times and lead to increased morbidity and mortality. The effects of hospital design and an interventional platform (IP) on patient care, particularly on the DTB time, are unknown. Methods: We performed a retrospective analysis of consecutive patients presenting to the emergency department of a medical center from September 2010 to February 2014 who met criteria for a ST-segment elevation myocardial infarction and underwent primary percutaneous coronary intervention. Patients were divided into 2 groups based on whether they presented before or after the opening of the IP in our new hospital on January 6, 2012. Total DTB time and separate systematic intervals were tabulated. Results: Fifty-two patients met our inclusion criteria, 21 pre-IP and 31 post-IP. Both groups had overall similar baseline characteristics. The mean DTB time significantly improved by 11.7 minutes after the opening of the IP (P = 0.016), and all cases had a DTB time 90 minutes or less as compared with 90.4% prior. Eighty-nine percent of the overall improvement in DTB happened before the patient reached the catheterization table. Important factors were the new emergency department (ED) design that facilitates rapid patient triage and the direct connection between the ED and cath lab. Conclusions: This study showed that the new hospital design had significant effects on immediate patient care by improving the DTB time at our institution. Further study regarding the long-term impact of hospital designs on patient care is needed.